Regulatory T cells in spondyloarthropathies: genetic evidence, functional role, and therapeutic possibilities - Rodolfi, Stefano; Davidson, Connor; Vecellio, Matteo (Frontiers in Immunology, 2024)
Regulatory T cells (Tregs) are a very specialized subset of T-lymphocytes: their main function is controlling immune responses during inflammation. T-regs involvement in autoimmune and immune-mediated rheumatic diseases is well-described. Here we critically review the up-to-date literature findings on the role of Tregs in spondyloarthropathies, particularly in ankylosing spondylitis (AS), a polygenic inflammatory rheumatic disease which preferentially affects the spine and the sacroiliac joints. Genetics discoveries helped in elucidating pathogenic T-regs gene modules and functional involvement. We highlight T-regs tissue-specificity as crucial point, as T-regs might have a distinct epigenomic and molecular profiling depending on the different site of tissue inflammation. Further, we speculate about possible therapeutic interventions targeting, or enhancing, Treg cells in spondyloarthropathies.